Sanility tolerant hybrids - CGIAR Research Program on Maize (2018)
A set of 305 experimental hybrids were evaluated under managed salinity stress at International Center for Bio-saline Agriculture (ICBA), Dubai, and top-ranking 5 promising crosses were identified, enough seed multiplied and shared with partners in Bangladesh (BARI and BRAC) for on-farm multilocation evaluation.